Analysis of the Impact of Network Quality, Brand Image, and Promotion on Telkomsel Package Card Purchase Decisions (Case Study on Students of SMK Brigadier General Katamso II Medan) - Pranata, Bayu; Tambunan, Debora; Sibarani, Hendra Jonathan; Pasaribu, Dompak (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study was conducted to determine the effect of network quality, brand image and promotion partially and simultaneously on purchasing decisions for Telkomsel package cards, a case study of students of SMK Brigjend Katamso II Medan. The research approach used is associative research with a quantitative approach. The population in this study consisted of all students of SMK Brigjend Katamso II Medan for the 2021/2022 academic year who used the Telkomsel provider as many as 90 students and the sampling technique used a saturated sample where the entire population was sampled, namely 90 people. This study uses primary data and secondary data. The results of this study network quality, brand image, and promotion partially have a positive effect on purchasing decisions. Simultaneous test results (F test) network quality, brand image and promotion have a positive and significant effect on purchasing decisions. The results of the determination test obtained that network quality, brand image and promotion have contributed to purchasing decisions by 66.1%, while the remaining 33.9% is influenced by other variables outside this regression model.